Error Correction Codes Performance using Binary Phase Shift Keying over Fading Channel - Hilal Hudan Nuha; Abdi T. Abdalla (International Journal on Information and Communication Technology (IJoICT), 2022)
In a communication system, two main resources are used: transmission power and channel bandwidth. Transmission power is the average power of the transmitted signal. Channel bandwidth is defined as the frequency band allocated for the transmission of the message signal. A goal of general system design is to use these two resources as efficiently as possible. This scientific paper presents the experimental results of the Binary Phase Shift Keying (BSK) communication system on the additive white gaussian noise (AWGN) channel and the Fading channel. To improve system performance, error correction code (ECC) is used for encoding. ECC used include convolutional code (ConvCode) and Hamming code. Experimental results show that for BER=10^(-4) the coding gain of the ConvCode over Hamming code under AWGN is G=0.475dB. Whereas the coding gain of the ConvCode over unencoded BPSK is G=19.6dB.